RETRACTED: The concept of regional sectoral development in modern trends of sustainability and digitalization - Nasser Muhammed Hussein; Solovyova Yuliana; Telyatnikova Victoria; Syrbu Anzhelika (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001